The possibility of originalism in Malaysia - Farid Sufian Shuaib; Fariza Milaqurshiah Mahmud (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper highlights the feasibility of originalism as a constitutional interpretive approach in Malaysia. A doctrinal method through case analysis along with comparative method is applied in this paper. Originalism finds its strength in stability of language through fidelity of the text. This is pertinent in increasing the possibility of coherence and mitigating arbitrariness amidst the contemporary challenges arising from rapid change of values. Through illustration of cases, this paper suggests that originalism may have been applied in the past. This paper also proposes some supporting measures to optimize the effectiveness of originalism in interpreting the Federal Constitution by the Malaysian Judiciary. The author concludes that originalism has a place in Malaysia and in fact, serves a very important role to preserve the country’s traditional values and traditional elements through fidelity to the text.